Ion transporter gene expression is linked to the thermal sensitivity of calcification in the reef coral Stylophora pistillata - Bernardet, C. (Sci Rep, 2019)
Coral calcification underpins biodiverse reef ecosystems, but the physiology underlying the thermal sensitivity of corals to changing seawater temperatures remains unclear. Furthermore, light is also a key factor in modulating calcification rates, but a mechanistic understanding of how light interacts with temperature to affect coral calcification is lacking. Here, we characterized the thermal performance curve (TPC) of calcification of the wide-spread, model coral species Stylophora pistillata, and used gene expression analysis to investigate the role of ion transport mechanisms in thermally-driven declines in day and nighttime calcification. Focusing on genes linked to transport of dissolved inorganic carbon (DIC), calcium and H(+), our study reveals a high degree of coherence between physiological responses (e.g. calcification and respiration) with distinct gene expression patterns to the different temperatures in day and night conditions. At low temperatures, calcification and gene expression linked to DIC transport processes were downregulated, but showed little response to light. By contrast, at elevated temperature, light had a positive effect on calcification and stimulated a more functionally diverse gene expression response of ion transporters. Overall, our findings highlight the role of mechanisms linked to DIC, calcium and H(+) transport in the thermal sensitivity of coral calcification and how this sensitivity is influenced by light.